Best local approximations by abstract norms with non-homogeneous dilations - Yanzon, Norma Beatriz (2008)
We introduce a concept of best local approximation using abstract norms and non-homogeneous dilations. The asymptotic behavior of the normalized error function as well as the limit of some net of best approximation polynomials Pε as ε → 0 are studied.